Review of Lung Cancer Detection and Classification Image Processing Techniques - Noreen Sarai; Wendy Gapare; Taurai George Rebanowako (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
The aim of this review is to present an overview of Lung Cancer Detection and Classification Using Digital Image Processing computer aided design systems. The discovery of cellular breakdown in the lungs through picture handling was a significant apparatus for the analysis. Several techniques were presented with the goal of having a thorough understanding of the techniques that are used during lung cancer detection. The techniques analysed in this review includes, CT scan examination, thresholding technique, nodule segmentation techniques, pre-processing and segmentation techniques and classification techniques. Models used during classification were also analysed with the goal of presenting a comprehensive analysis of these techniques as they are used during lung cancer detection. CAD was found to be the most popular technique being used.